Anatomical variations in epididymal–testicular fusion in stallions and their possible clinical significance. (23rd July 2015) - Pozor, M.; Freeman, D.; Troedsson, M.; Brown, M.; Morton, A.; Smith, A.; McNaughten, J.
Summary: Reasons for performing study: Fusion anomalies of the epididymis with the testis may be clinically relevant in horses. However, anatomical variations in epididymal–testicular fusion have not been classified, and their clinical significance is unknown. Objectives: To describe anatomical variations and clinical significance of epididymal–testicular fusion in stallions. Study design: Anatomical study of testes from castrations, and description of 2 clinical cases with atypical epididymal–testicular fusion. Methods: A total of 104 testes were obtained from equine castrations. Eight patterns of epididymal–testicular fusion were identified. Two clinical cases with epididymal dislocation were also described. Results: Close attachment of the entire epididymis to the testis was the most common pattern of fusion (40%). Ninety‐five per cent of cryptorchid testes and 34% of scrotal testes in the studied sample had elongated proper ligaments of the testes. Dislocation of the epididymal tail was observed in 2 stallions that had atypically long proper ligaments inserted on the dorsal aspect of the testes. Conclusions: Patterns of epididymal–testicular fusion can vary in stallions. Elongated proper ligaments of the testes occur mostly in cryptorchid testes but are also found in stallions with scrotal testes. Epididymal dislocation may develop in stallions with long proper ligaments that are inserted dorsally on the testes.